Treatment of Periodontal Intrabony Defect by Open Flap Debridement With or Without Platelet-rich Fibrin - Adhikari, Binod; Pradhan, Shaili; Shrestha, Sweta (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Introduction: Periodontitis is a chronic bacterial infection leading to destruction of supporting structures of teeth which may ultimately result in a variety of periodontal intraosseous defects. Goal of periodontal therapy is to regenerate lost periodontal tissue for optimal function and aesthetics. Platelet-rich concentrates are widely being used as regenerative biomaterials as they stimulate and accelerate healing by continuous release of growth factors. Objective: To evaluate the clinical efficacy of autologous platelet-rich fibrin (PRF) along with open flap debridement (OFD) or OFD alone in the treatment of periodontal intrabony defects. Methods: This non-randomised clinical study was conducted from June 2015 - May 2016 at Bir Hospital. Patients diagnosed with Chronic Periodontitis were selected using convenience sampling and divided into two groups: Control (OFD only) and Test (OFD+PRF) with 16 in each group. All subjects underwent periodontal examination by a single examiner. The periodontal parameters were assessed and compared between control and test groups at baseline and six months. Data analysis was done using SPSS 22 software program. Results: The mean PI scores, GI scores, PD reduction, and CAL gain scores improved in both control and test groups at six months compared to baseline. The comparison of mean difference for every parameter measured showed statistically significant difference (p <0.05) at baseline and after six months for both the groups. However, the results were superior in the test group. Conclusions: The addition of autologous PRF to OFD stimulated a significant improvement in the clinical parameters as compared to OFD alone at six months.